The Effect of Efficiency and Cost Changes in Labor Factor on Physical Capital Investments: Dynamic Panel Data Analysis - Ali İhsan Öztürk (Sosyal Siyaset Konferansları Dergisi)
Economic growth is simply the increase in the amount of goods and services produced as the production capacity of a country’s economy increases. Production is possible by bringing together factors of production such as physical capital, human capital, labor, and natural resources by entrepreneurs. Labor, one of these factors, refers to the physical and mental human contribution used in the production process. The amount of labor to be used in the production process may vary depending on the efficiency and costs of this factor. In this paper, the effects of changes in efficiency and costs of the labor factor on physical capital investments are investigated. In the study where the Dynamic Panel Data Method was applied; annual data of 22 selected European Union member countries and Turkey covering the period between 2006-2019 were used. According to the results obtained with Two-Stage GMM and Two-Stage System GMM estimators, there is a positive relationship between physical capital investments and labor efficiency. On the other hand, the labor cost and the 2008 global financial crisis negatively affect physical capital investments. Especially in terms of labor efficiency, it is suggested that human capital and technology investments should be considered as priority policies.